Pore characteristics of physical crust samples from two typical erodible soils in southern China. (17th April 2022) - Zhu, Xuchao; Liang, Yin; Cao, Longxi; Tian, Zhiyuan; Li, Meng
Abstract: Physical soil crusts will form on most soils during and after rainfall, which has important impacts on hydrological and erosion processes by affecting soil pore structure. However, the soil pore characteristics of physical crusts of two typical erodible soils (quaternary red clay [QRC] and granite red soil [GRS]) in southern China are still unclear due to the limitations of objective and accurate quantitative methods. We scanned physical crusted (structural crust [SC] and depositional crust [DC]) soil samples from the QRC and GRS at various slopes using X‐ray computed tomography, and extracted and analysed soil pore characteristics using two‐ and three‐dimensional indexes. The averages of the two‐dimensional pore indexes, that is, pore number, porosity, circularity, and equivalent diameter across the four soil sample types were 116–205, 4.83%–8.31%, 0.83–0.87, and 0.19–0.28 mm, respectively, indicating the characteristics of a large number of small pores with nearly circular shape. The mean values of pore number and circularity were significantly smaller for the structural crust samples than the depositional crust samples, and the porosity and equivalent diameter were significantly larger for the structural crust samples than the depositional crust samples. The three‐dimensional pore indexes also differed among the four soil sample types, where the mean fractal dimension and surface area values for QRC were 2.62 and 1959.77 mm 2, respectively, which were significantly larger than those for GRS (2.52 and 1457.97 mm 2 ). The pore number and circularity decreased, the equivalent diameter increased, and the surface area and connectivity density increased initially and then decreased with the slope, mainly due to differences in the run‐off and sediment process, and crust formation process on slopes with different gradients. The results provide a scientific basis for the objective quantification of physical soil crusts to facilitate further studies on physical crusts affect run‐off and sediment processes. Highlights: CT method was first used to quantify pore structure of crusted soil samples in southern China. The crusted soil pores had a feature of a large number of small pores with nearly circular shape. The two‐ and three‐dimensional soil pore indexes were differed among the four soil sample types. The slope had a negligible influence on soil pore structure.